Wear-resistant water-based finish paint capable of resisting hand perspiration and preparation method thereof

By using aqueous acrylic dispersion containing hydroxyl functional groups and epoxy resin with alcohol hydroxyl groups in the aqueous wood paint for esterification, combined with aqueous aliphatic polyether polyurethane and lipoic acid, the existing aqueous wood paint is not resistant to hand sweat and does not have the ability to self-heal, and the effect of anti-hand sweat, wear resistance and self-healing is achieved.

CN119752325APending Publication Date: 2025-04-04DONGGUAN TUBA NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411946811.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing water-based wood paint is not resistant to hand sweat, is prone to sweat stains, and does not have self-repair ability and wear resistance, which affects the use experience and appearance of furniture.

Method used

An esterification reaction is carried out using an aqueous acrylic dispersion containing hydroxyl functional groups and an epoxy resin with alcohol hydroxyl groups, combined with aqueous aliphatic polyether polyurethane and lipoic acid to prepare a wear-resistant water-resistant topcoat that resists hand sweat.

Benefits of technology

This water-based topcoat is not easy to leave watermarks or sweat marks, has a full matte effect, has self-repair ability and excellent wear resistance, and can slowly rebound and repair after being scratched.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses wear-resistant water-based finish paint capable of resisting hand perspiration. Comprising the following components in parts by weight: 50-55 parts of a water-based acrylic dispersion containing hydroxyl functional groups, 20-25 parts of a water-based aliphatic polyether polyurethane dispersion, 15-25 parts of epoxy resin with alcoholic hydroxyl groups, 5-10 parts of water, 1-5 parts of lipoic acid, 0.3-0.8 part of a first defoaming agent, 10-25 parts of water-based titanium dioxide slurry, 0.2-0.5 part of a flatting agent, 0.5-0.8 part of a wetting agent, 0.2-0.4 part of a first dispersing agent and 0.7-4 parts of water-based color paste, 0.5 to 1.3 parts of a thickening agent; the main components are water-based materials, so that the prepared finish paint is very hydrophilic, watermarks or sweat marks are not easy to leave, the obtained ester compound is acrylate with an epoxy group and has a matting effect, the prepared finish paint can be fully matte, polyether polyurethane has excellent elasticity and flexibility, stress can be dispersed through the elasticity, and therefore abrasion is reduced, and the finish paint can be used as a water-based finish paint. And moreover, the epoxy resin with the alcoholic hydroxyl group reacts with lipoic acid to generate a reversible disulfide bond, so that the finish paint has a self-repairing capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the coating field technology, in particular to an anti-hand sweat wear-resistant water-based topcoat and a preparation method thereof. Background Art

[0002] With the rapid development of my country's social economy, consumers have higher and higher requirements for quality of life. In terms of wood decoration and furniture purchase, the demand for high-end solid wood furniture is much higher than that for panel furniture or artificial board furniture.

[0003] Water-based wood paint is a polymer material that uses water as a dispersion medium instead of organic solvents in traditional oil-based paints. It has the advantages of being non-toxic, pollution-free, low odor, non-flammable and non-explosive. However, the water-based full-matte solid-color wood paint on the market is not resistant to hand sweat. During transportation, the weather is hot and the hands sweat a lot. If you touch the surface of the furniture directly with your hands, it is easy to get these sweat stains on the furniture. If you don’t take protective measures, it is easy for the furniture with a smooth surface to have stains, and the sweat stains are difficult to clean, and the more you wipe, the dirtier it will get. In addition, sweat stains will also destroy the original touch of the furniture surface and affect the user experience. The topcoat is not wear-resistant and does not have self-repairing ability, so it is easy to leave marks on the furniture after scratching, affecting the appearance. Therefore, it is necessary to propose a new solution to the above problems. Summary of the invention

[0004] In view of this, the present invention aims at the deficiencies in the prior art, and its main purpose is to provide an anti-hand sweat wear-resistant water-based topcoat and a preparation method thereof, which can effectively solve the problem that the existing furniture topcoats do not have anti-hand sweat performance and self-repairing ability, and are not wear-resistant.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A hand sweat-resistant wear-resistant water-based topcoat comprises the following components in parts by weight:

[0007] 50-55 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 20-25 parts of aqueous aliphatic polyether polyurethane dispersion, 15-25 parts of epoxy resin having alcoholic hydroxyl groups, 5-10 parts of water, 1-5 parts of thioctic acid, 0.3-0.8 parts of a first defoamer, 10-25 parts of aqueous titanium dioxide, 0.2-0.5 parts of a leveling agent, 0.5-0.8 parts of a wetting agent, 0.2-0.4 parts of a first dispersant, 0.7-4 parts of an aqueous colorant, and 0.5-1.3 parts of a thickener;

[0008] The weight percentages of the components in each portion of aqueous titanium dioxide slurry are: 1-2% of auxiliary solvent, 12-18% of water, 4-8% of second dispersant, 0.3-0.8% of second defoamer, and 70-75% of titanium dioxide.

[0009] As a preferred solution, the model of the aqueous acrylic dispersion containing hydroxyl functional groups is AlberdingkAC2592.

[0010] As a preferred solution, the model of the aqueous aliphatic polyether polyurethane dispersion is AlberdingkU4040VP.

[0011] As a preferred embodiment, the water is purified water or deionized water, and the first defoaming agent and the second defoaming agent are both polydimethylsiloxane.

[0012] As a preferred solution, the leveling agent is polyether siloxane, and the wetting agent is polyether modified siloxane or multifunctional modified siloxane.

[0013] As a preferred solution, the model of the first dispersant and the model of the second dispersant are both BYK190, and the water-based colorant is the SI series colorant produced by Cordina Micro New Materials Co., Ltd.

[0014] As a preferred solution, the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0015] A method for preparing the aforementioned anti-hand sweat wear-resistant water-based topcoat comprises the following steps:

[0016] (1) taking 10-15 parts of an epoxy resin having an alcoholic hydroxyl group and 20-30 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0017] (2) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 60-120° C., stirring and reacting for 60-180 minutes, to obtain an epoxy compound;

[0018] (3) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 20-30 minutes, and detect the fineness to be ≤25 μm to obtain a water-based titanium dioxide slurry;

[0019] (4) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 20-30 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0020] (5) The test fineness is less than or equal to 25 μm;

[0021] (6) pH = 7.5-9;

[0022] (7) Spraying has no shrinkage holes and other adverse paint film effects.

[0023] (8) Detection gloss ≤ 5°;

[0024] (9) Take out the finished product after passing the inspection.

[0025] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0026] The main components are all water-based materials, which makes the prepared topcoat very hydrophilic and not easy to leave watermarks or sweat marks. The ester compound obtained by esterifying the epoxy resin with alcoholic hydroxyl groups and the water-based acrylic dispersion containing hydroxyl functional groups is an acrylate with epoxy groups, which has a matting effect, so that the prepared topcoat can achieve full matte. At the same time, there is no need to add silica for matting, which prevents the topcoat from reducing the water drop angle of the paint surface due to the presence of silica, making the topcoat not stain-resistant and reducing the anti-hand sweat performance. In addition, polyether polyurethane has excellent elasticity and flexibility. Elasticity can disperse stress, thereby reducing wear and tear, and can slowly rebound and repair after being scratched. In addition, the epoxy resin with alcoholic hydroxyl groups reacts with lipoic acid to form a reversible disulfide bond, which makes the topcoat have self-repairing ability.

[0027] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION

[0028] The present invention discloses a wear-resistant water-based topcoat that resists hand sweat, comprising the following components in parts by weight:

[0029] 50-55 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 20-25 parts of aqueous aliphatic polyether polyurethane dispersion, 15-25 parts of epoxy resin having alcoholic hydroxyl groups, 5-10 parts of water, 1-5 parts of thioctic acid, 0.3-0.8 parts of a first defoamer, 10-25 parts of aqueous titanium dioxide, 0.2-0.5 parts of a leveling agent, 0.5-0.8 parts of a wetting agent, 0.2-0.4 parts of a first dispersant, 0.7-4 parts of an aqueous colorant, and 0.5-1.3 parts of a thickener;

[0030] The weight percentages of the components in each portion of aqueous titanium dioxide slurry are: 1-2% of auxiliary solvent, 12-18% of water, 4-8% of second dispersant, 0.3-0.8% of second defoamer, and 70-75% of titanium dioxide.

[0031] Among them, the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is purified water or deionized water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is polyether modified siloxane or multifunctional modified siloxane, the model of the first dispersant and the model of the second dispersant are both BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0032] The present invention discloses a method for preparing the aforementioned anti-hand sweat wear-resistant water-based topcoat, comprising the following steps:

[0033] (1) taking 10-15 parts of an epoxy resin having an alcoholic hydroxyl group and 20-30 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0034] (2) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 60-120° C., stirring and reacting for 60-180 minutes, to obtain an epoxy compound;

[0035] (3) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 20-30 minutes, and detect the fineness to be ≤25 μm to obtain a water-based titanium dioxide slurry;

[0036] (4) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 20-30 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0037] (5) The test fineness is less than or equal to 25 μm;

[0038] (6) pH = 7.5-9;

[0039] (7) Spraying has no shrinkage holes and other adverse paint film effects.

[0040] (8) Detection gloss ≤ 5°;

[0041] (9) Take out the finished product after passing the inspection.

[0042] The following describes the invention in conjunction with specific embodiments.

[0043] Example 1

[0044] (1) Prepare the following raw materials: 50 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 20 parts of aqueous aliphatic polyether polyurethane dispersion, 15 parts of epoxy resin having alcoholic hydroxyl groups, 5 parts of water, 1 part of thioctic acid, 0.3 parts of a first defoamer, 10 parts of aqueous titanium dioxide slurry, 0.2 parts of a leveling agent, 0.5 parts of a wetting agent, 0.2 parts of a first dispersant, 0.7 parts of an aqueous color paste, and 0.5 parts of a thickener;

[0045] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 2% co-solvent, 18% water, 8% second dispersant, 0.8% second defoamer, and 71.2% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is purified water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is polyether modified siloxane, the model of the first dispersant and the model of the second dispersant are BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0046] (2) taking 10 parts of an epoxy resin having an alcoholic hydroxyl group and 30 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0047] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 60° C., stirring and reacting for 60 minutes to obtain an epoxy compound;

[0048] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 25 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0049] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 20 minutes to obtain a water-based topcoat that is resistant to hand sweat;

[0050] (6) The test fineness is less than or equal to 25 μm;

[0051] (7) pH = 7.5-9;

[0052] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0053] (9) Detection gloss ≤ 5°;

[0054] (10) Take out the finished product after passing the inspection.

[0055] Example 2

[0056] (1) Prepare the following raw materials: 55 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 25 parts of aqueous aliphatic polyether polyurethane dispersion, 25 parts of epoxy resin having alcoholic hydroxyl groups, 10 parts of water, 5 parts of thioctic acid, 0.8 parts of a first defoamer, 25 parts of aqueous titanium dioxide slurry, 0.5 parts of a leveling agent, 0.8 parts of a wetting agent, 0.4 parts of a first dispersant, 4 parts of an aqueous color paste, and 1.3 parts of a thickener;

[0057] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 1.7% co-solvent, 17% water, 6% second dispersant, 0.3% second defoamer, and 75% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is deionized water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is a multifunctional modified siloxane, the model of the first dispersant and the model of the second dispersant are both BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0058] (2) taking 15 parts of an epoxy resin having an alcoholic hydroxyl group and 20 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0059] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid, stirring and mixing them uniformly at room temperature, heating to 120° C., stirring and reacting for 180 minutes, to obtain an epoxy compound;

[0060] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 30 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0061] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 30 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0062] (6) The test fineness is less than or equal to 25 μm;

[0063] (7) pH = 7.5-9;

[0064] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0065] (9) Detection gloss ≤ 5°;

[0066] (10) Take out the finished product after passing the inspection.

[0067] Example 3

[0068] (1) Prepare the following raw materials: 52 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 24 parts of aqueous aliphatic polyether polyurethane dispersion, 20 parts of epoxy resin having alcoholic hydroxyl groups, 8 parts of water, 3 parts of thioctic acid, 0.5 parts of a first defoamer, 20 parts of aqueous titanium dioxide slurry, 0.2 parts of a leveling agent, 0.5 parts of a wetting agent, 0.2 parts of a first dispersant, 0.7 parts of an aqueous colorant, and 0.5 parts of a thickener;

[0069] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 1.5% co-solvent, 18% water, 4% second dispersant, 0.5% second defoamer, and 71% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is purified water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is polyether modified siloxane, the model of the first dispersant and the model of the second dispersant are BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0070] (2) taking 15 parts of an epoxy resin having an alcoholic hydroxyl group and 20 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0071] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid, stirring and mixing them uniformly at room temperature, heating to 80° C., stirring and reacting for 80 minutes, to obtain an epoxy compound;

[0072] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 25 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0073] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 25 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0074] (6) The test fineness is less than or equal to 25 μm;

[0075] (7) pH = 7.5-9;

[0076] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0077] (9) Detection gloss ≤ 5°;

[0078] (10) Take out the finished product after passing the inspection.

[0079] Example 4

[0080] (1) Prepare the following raw materials: 51 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 23 parts of aqueous aliphatic polyether polyurethane dispersion, 25 parts of epoxy resin having alcoholic hydroxyl groups, 8 parts of water, 5 parts of thioctic acid, 0.5 parts of a first defoamer, 20 parts of aqueous titanium dioxide slurry, 0.5 parts of a leveling agent, 0.8 parts of a wetting agent, 0.4 parts of a first dispersant, 4 parts of an aqueous color paste, and 1.3 parts of a thickener;

[0081] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 2% co-solvent, 16% water, 6.7% second dispersant, 0.3% second defoamer, and 75% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is deionized water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is a multifunctional modified siloxane, the model of the first dispersant and the model of the second dispersant are both BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0082] (2) taking 15 parts of an epoxy resin having an alcoholic hydroxyl group and 30 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0083] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 70° C., stirring and reacting for 100 minutes, to obtain an epoxy compound;

[0084] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 25 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0085] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 25 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0086] (6) The test fineness is less than or equal to 25 μm;

[0087] (7) pH = 7.5-9;

[0088] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0089] (9) Detection gloss ≤ 5°;

[0090] (10) Take out the finished product after passing the inspection.

[0091] Example 5

[0092] (1) Prepare the following raw materials: 50 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 25 parts of aqueous aliphatic polyether polyurethane dispersion, 15 parts of epoxy resin having alcoholic hydroxyl groups, 10 parts of water, 1 part of thioctic acid, 0.3 parts of a first defoamer, 20 parts of aqueous titanium dioxide slurry, 0.2 parts of a leveling agent, 0.5 parts of a wetting agent, 0.2 parts of a first dispersant, 2 parts of an aqueous color paste, and 0.5 parts of a thickener;

[0093] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 2% co-solvent, 18% water, 7.5% second dispersant, 0.5% second defoamer, and 72% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is purified water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is polyether modified siloxane, the model of the first dispersant and the model of the second dispersant are BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0094] (2) taking 10 parts of an epoxy resin having an alcoholic hydroxyl group and 25 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0095] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 100° C., stirring and reacting for 60 minutes to obtain an epoxy compound;

[0096] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 20 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0097] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 30 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0098] (6) The test fineness is less than or equal to 25 μm;

[0099] (7) pH = 7.5-9;

[0100] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0101] (9) Detection gloss ≤ 5°;

[0102] (10) Take out the finished product after passing the inspection.

[0103] Example 6

[0104] (1) Prepare the following raw materials: 51 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 20 parts of aqueous aliphatic polyether polyurethane dispersion, 18 parts of epoxy resin having alcoholic hydroxyl groups, 8 parts of water, 2 parts of thioctic acid, 0.5 parts of a first defoamer, 22 parts of aqueous titanium dioxide slurry, 0.2 parts of a leveling agent, 0.5 parts of a wetting agent, 0.2 parts of a first dispersant, 3 parts of an aqueous color paste, and 1 part of a thickener;

[0105] Among them, the weight percentage of each component in each aqueous titanium dioxide slurry is: 2% co-solvent, 18% water, 4.2% second dispersant, 0.8% second defoamer, and 75% titanium dioxide; the model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592, the model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP, the water is purified water, the first defoamer and the second defoamer are both polydimethylsiloxane, the leveling agent is polyether siloxane, the wetting agent is polyether modified siloxane, the model of the first dispersant and the model of the second dispersant are BYK190, the aqueous color paste is the SI series color paste produced by Cordina Micro New Materials Co., Ltd., the thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

[0106] (2) taking 12 parts of an epoxy resin having an alcoholic hydroxyl group and 20 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound;

[0107] (3) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid, stirring and mixing them uniformly at room temperature, heating to 80° C., stirring and reacting for 120 minutes, and obtaining an epoxy compound;

[0108] (4) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 25 minutes, and detect that the fineness is ≤25 μm to obtain a water-based titanium dioxide slurry;

[0109] (5) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 25 minutes to obtain an anti-sweat wear-resistant water-based topcoat;

[0110] (6) The test fineness is less than or equal to 25 μm;

[0111] (7) pH = 7.5-9;

[0112] (8) Spraying has no shrinkage holes and other adverse paint film effects.

[0113] (9) Detection gloss ≤ 5°;

[0114] (10) Take out the finished product after passing the inspection.

[0115] The above multiple embodiments were tested, the test method is as follows, and the test results are shown in Table 1.

[0116] Friction test: Use a felt paper test head to rub back and forth in the middle of the printed characters or patterns, and move a distance of 10mm with a driving force of 4N for ≥15,000 times to observe whether the characters have paint peeling.

[0117] Hand sweat resistance test: Use a dust-free cloth soaked in sweat with a pH of 2.6 to stick it on the surface of the sample and seal it with a sealing plastic bag and store it in a constant temperature and humidity chamber at a temperature of 55±1℃ and a humidity of 93±2%RH for 48 hours. After the test, return to normal temperature for at least 2 hours, wipe off the solution on the surface of the product and check whether the product appearance has discoloration, blistering, or corrosion.

[0118] Self-repair performance test: Use a blunt object to scratch a mark on the paint surface, blow hot air on the mark for 10 minutes, observe whether the mark recovers, and what is the temperature of the hot air in degrees Celsius.

[0119] Whether the paint is peeling Whether to change color Whether it foams Is it corroded? Restore Hot air temperature Example 1 no no no no yes 45℃ Example 2 no no no no yes 42℃ Example 3 no no no no yes 50℃ Example 4 no no no no yes 46℃ Example 5 no no no no yes 42℃ Example 6 no no no no yes 44℃

[0120] Table 1

[0121] By observing the above data, it is obvious that the water-based topcoat prepared using the formula and preparation method of the present invention has excellent wear resistance, and the anti-hand sweat performance and self-repairing ability are also very excellent.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A wear-resistant water-based topcoat that resists hand sweat, characterized in that: It includes the following components in parts by weight: 50-55 parts of aqueous acrylic dispersion containing hydroxyl functional groups, 20-25 parts of aqueous aliphatic polyether polyurethane dispersion, 15-25 parts of epoxy resin having alcoholic hydroxyl groups, 5-10 parts of water, 1-5 parts of thioctic acid, 0.3-0.8 parts of a first defoamer, 10-25 parts of aqueous titanium dioxide, 0.2-0.5 parts of a leveling agent, 0.5-0.8 parts of a wetting agent, 0.2-0.4 parts of a first dispersant, 0.7-4 parts of an aqueous colorant, and 0.5-1.3 parts of a thickener; The weight percentages of the components in each portion of aqueous titanium dioxide slurry are: 1-2% of auxiliary solvent, 12-18% of water, 4-8% of second dispersant, 0.3-0.8% of second defoamer, and 70-75% of titanium dioxide.

2. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The model of the aqueous acrylic dispersion containing hydroxyl functional groups is Alberdingk AC2592.

3. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The model of the aqueous aliphatic polyether polyurethane dispersion is Alberdingk U4040VP.

4. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The water is pure water or deionized water, and the first defoamer and the second defoamer are both polydimethylsiloxane.

5. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The leveling agent is polyether siloxane, and the wetting agent is polyether modified siloxane or multifunctional modified siloxane.

6. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The model of the first dispersant and the model of the second dispersant are both BYK190, and the water-based colorant is the SI series colorant produced by Cordina Micro New Materials Co., Ltd.

7. The anti-hand sweat wear-resistant water-based topcoat according to claim 1, characterized in that: The thickener is associative polyurethane, and the model of the titanium dioxide is R-706.

8. A method for preparing an anti-sweat wear-resistant water-based topcoat according to any one of claims 1 to 7, characterized in that: The following steps are included: (1) taking 10-15 parts of an epoxy resin having an alcoholic hydroxyl group and 20-30 parts of an aqueous acrylic dispersion containing a hydroxyl functional group, and performing an esterification reaction to obtain an ester compound; (2) taking the remaining epoxy resin having alcoholic hydroxyl groups and lipoic acid and stirring and mixing them uniformly at room temperature, heating to 60-120° C., stirring and reacting for 60-180 minutes, to obtain an epoxy compound; (3) Under normal temperature conditions, add a cosolvent, water, a second dispersant, a second defoamer, and titanium dioxide into a high-speed disperser according to percentages, stir at high speed for 20-30 minutes, and detect the fineness to be ≤25 μm to obtain a water-based titanium dioxide slurry; (4) at room temperature, the ester compound obtained in step (1), the epoxy compound obtained in step (2), the aqueous titanium dioxide slurry obtained in step (3) and the remaining components are placed in a high-speed disperser and stirred for 20-30 minutes to obtain an anti-sweat wear-resistant water-based topcoat; (5) The test fineness is less than or equal to 25 μm; (6) pH = 7.5-9; (7) There are no shrinkage holes or other poor paint film effects during spraying; (8) The gloss is tested to be ≤5°; (9) Take out the finished product after passing the inspection.

Citation Information

Patent Citations

  • Wood varnish as well as preparation method and application method of wood varnish

    CN104592877A

  • A preparing method of water-based self-crosslinking acrylic acid modified polyurethane matte resin

    CN105694651A

  • High-hardness and scratching resistant two-component waterborne wood matte varnish and preparation method thereof

    CN106833332A

  • Solvent-free self-repairing epoxy resin and preparation method thereof

    CN109233571A

  • Waterborne bicomponent modified polyurethane industrial coating and preparation method thereof

    CN109321117A

Cited By

  • Anti-static dust-free cloth and preparation method thereof

    CN121896829A